2020
DOI: 10.1021/acs.energyfuels.0c00456
|View full text |Cite
|
Sign up to set email alerts
|

Pore Systems of the Different Lithofacies of the Longmaxi Formation at Depths Exceeding 3500 m in the Zigong Area, Sichuan Basin

Abstract: The deep Longmaxi Formation shale in the Zigong area is widely distributed and has a huge resource potential, which has enabled it to become one of the most important replacement areas for shale gas exploration in China. This article investigates the key shale gas evaluation well, Well Z1, in the Zigong area using field emission-scanning electron microscopy, mercury intrusion capillary pressure, low-pressure N2/CO2 adsorption, and fractal theory to determine the pore systems of the different lithofacies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…It is interesting to observe that all of the samples exhibit hysteresis loops, formed by the divergence between adsorption and desorption curves (Figure ). The shape and size of hysteresis loops in marine shales indicate that pores are mainly inkbottle-shaped and the pore structure may be more complicated than other samples. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to observe that all of the samples exhibit hysteresis loops, formed by the divergence between adsorption and desorption curves (Figure ). The shape and size of hysteresis loops in marine shales indicate that pores are mainly inkbottle-shaped and the pore structure may be more complicated than other samples. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The shape and size of hysteresis loops in marine shales indicate that pores are mainly inkbottle-shaped and the pore structure may be more complicated than other samples. 20,44,45 Based on the BJH model, the pore parameters of shale samples are extracted from N 2 adsorption (Table 2). The pore volumes of marine shales vary from 19.85 × 10 −3 to 34.63 × 10 −3 cm 3 /g, with an average of 29.27 × 10 −3 cm 3 /g.…”
Section: Resultsmentioning
confidence: 99%
“…Plus, how to recognize the effective reservoir types especially in the deep shale gas reservoirs is still unclear. 163 The research foundation in the regional scale is so weak in terms of diagenesis, diagenetic evolution, reservoir type, and pore system, together with organic−inorganic interactions, that the problem has become one of the important factors impeding the progress of shale gas exploration and development. With the generation and expulsion of hydrocarbon coupled with the pressure changes in the shale reservoirs, how did the organic and mineral pores interact and coevolve?…”
Section: Geological Challenges For Identifying Shale Gas Sweet Spot I...mentioning
confidence: 99%
“…The method of assigning weight considers little about shale diagenesis, reservoir type, pore structure, and pressure. Plus, how to recognize the effective reservoir types especially in the deep shale gas reservoirs is still unclear . The research foundation in the regional scale is so weak in terms of diagenesis, diagenetic evolution, reservoir type, and pore system, together with organic–inorganic interactions, that the problem has become one of the important factors impeding the progress of shale gas exploration and development.…”
Section: Geological Challenges For Identifying Shale Gas Sweet Spot I...mentioning
confidence: 99%
“…Based on the observation of the FHH model fitting lines on the adsorption isotherms in different samples, , it is found that there is no uniform method for dividing the adsorption isotherms when this model was applied. Moreover, the division method has great effect on the calculation result of the fractal dimension.…”
Section: Introductionmentioning
confidence: 99%